Dasar-Dasar Ilmu Jarh Wa Ta’didil - Ali Imron (Mukaddimah: Jurnal Studi Islam, 2018)
This paper discusses about science of jarh wa ta’dil, which contains the fundamentals of jarh wa ta’dil, from the definition, theological-rational basis, the History of Development from the Beginning, the terms and conditions, the ethics, the rules, the stages of jarh wa ta’dil, the characters, to the literature-literature used in science jarh ta’dil itself.